PENGARUH PERUBAHAN EARNING PER SHARE, DEBT TO EQUITY RATIO, DAN UKURAN PERUSAHAAN PADA RETURN SAHAM - Purwaningrat, Putu Atim; Suaryana, IGN Agung (E-Jurnal Akuntansi, 2015)
Stock returns are the gains an investor in making an investment as a result of the difference between the sales price and the purchase price. Information profitability so have relevance in estimating returns. This study aims to investigate the influence of changes in EPS, DER, and the size of the company on the stock return of companies in Indonesia Stock Exchange 2011-2013. Based on the criteria in the purposive sampling technique then obtained a sample of 768 companies. The results of the analysis of data based on multiple linear regression found that the partial change of EPS positive effect on stock returns. Variable DER negative effect of firm size variable whereas a positive effect on stock returns.
Keywords: EPS, DER, SIZE, stock returns